2016
DOI: 10.1093/jat/bkw078
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine Carboxylic Acid and Quetiapine Sulfoxide Prevalence in Patient Urine

Abstract: Treatment adherence is often an issue with mental health patients. For those prescribed quetiapine (Seroquel), the low levels of parent drug and plasma metabolite(s) (e.g., 7-hydroxyquetiapine) typically used in urine drug monitoring can result in false negatives with concomitant unfavorable impacts on patient care. Literature review coupled with liquid chromatography/time-of-flight mass spectrometry analysis of patient positive urine samples indicated the presence of quetiapine carboxylic acid and quetiapine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The inclusion of quetiapine sulfoxide measurement in urine along with other analytes improved the adherence from 31% to 48%. Therefore, quetiapine sulfoxide due to its longer residence and larger systemic availability may provide an opportunity for a possible drug-drug interaction [21]. Secondly, in the case of triclabendazole sulfoxide, it was noted that the circulatory concentrations of the metabolite (peak concentration: 38.6 uM) far exceeded the observed concentration of the parent drug triclabendazole (peak concentration: 1.16 uM) following a standard dose of triclabendazole of 10 mg/kg in humans to treat trematode infestations such as Fascioliasis and Paragonimiasis [22].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of quetiapine sulfoxide measurement in urine along with other analytes improved the adherence from 31% to 48%. Therefore, quetiapine sulfoxide due to its longer residence and larger systemic availability may provide an opportunity for a possible drug-drug interaction [21]. Secondly, in the case of triclabendazole sulfoxide, it was noted that the circulatory concentrations of the metabolite (peak concentration: 38.6 uM) far exceeded the observed concentration of the parent drug triclabendazole (peak concentration: 1.16 uM) following a standard dose of triclabendazole of 10 mg/kg in humans to treat trematode infestations such as Fascioliasis and Paragonimiasis [22].…”
Section: Discussionmentioning
confidence: 99%
“…9 Strickland et al 9 reported that both the carboxylic acid and the sulfoxide of QTP were present at very high levels which were unaffected by hydrolysis. 10 Again, the carboxylic acid of QTP is available commercially for these analyses. 11 The impact of choosing a more prevalent metabolite for analysis is clearly demonstrated with the authors' choice of 7-hydroxychlorpromazine (HOCPZ) for analysis of chlorpromazine.…”
mentioning
confidence: 99%